Increasing Rates of Diagnosis, Substantial Co-Occurrence, and Variable Treatment Patterns of Eosinophilic Gastritis, Gastroenteritis, and Colitis Based on 10-Year Data Across a Multicenter Consortium. (June 2019) - Pesek, Robert D.; Reed, Craig C.; Muir, Amanda B.; Fulkerson, Patricia C.; Menard-Katcher, Calies; Falk, Gary W.; Kuhl, Jonathan; Martin, Ellen K.; Magier, Adam Z.; Ahmed, Faria; Demarshall, Maureen; Gupta, Ankur; et al.
Abstract : OBJECTIVES: The literature related to eosinophilic gastritis (EG), gastroenteritis (EGE), and colitis (EC) is limited. We aimed to characterize rates of diagnosis, clinical features, and initial treatments for patients with EG, EGE, and EC. METHODS: In this retrospective study, data were collected from 6 centers in the Consortium of Eosinophilic Gastrointestinal Researchers from 2005 to 2016. We analyzed demographics, time trends in diagnosis, medical history, presenting symptoms, disease overlap, and initial treatment patterns/responses. RESULTS: Of 373 subjects (317 children and 56 adults), 38% had EG, 33% EGE, and 29% EC. Rates of diagnosis of all diseases increased over time. There was no male predominance, and the majority of subjects had atopy. Presenting symptoms were similar between diseases with nausea/vomiting and abdominal pain, the most common. One hundred fifty-four subjects (41%) had eosinophilic inflammation outside of their primary disease location with the esophagus the second most common gastrointestinal (GI) segment involved. Multisite inflammation was more common in children than in adults (68% vs 37%; P < 0.001). Initial treatment patterns varied highly between centers. One hundred-nine subjects (29%) had follow-up within 6 months, and the majority had clinical, endoscopic, and histologic improvements. CONCLUSIONS: In this cohort, EG, EGE, and EC were diagnosed more frequently over time, and inflammation of GI segments outside the primary disease site co-occurrence of atopy was common with a lack of male predominance. Symptoms were similar between diseases, and initial treatment strategies were highly variable. Future investigation should assess the cause of the increased prevalence of eosinophilic GI disorders and prospectively assess outcomes to establish treatment algorithms.